Simplify this expression -(4y-8)+9=

Question

Asked 2/23/2012 11:54:44 AM

Updated 8/15/2015 11:25:16 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by jeifunk [8/15/2015 11:25:16 AM]

s

Rating

8

-(4y-8)+9

=( - 4y) + (8 + 9)

= - 4y + 17

=( - 4y) + (8 + 9)

= - 4y + 17

Added 8/15/2015 11:25:12 AM

This answer has been confirmed as correct and helpful.

divide and simplify 12/5 divided by 7/2 = **Weegy:** (r^2) / (r^12)=r^2-12=r^-10
The answer is r^-10 or r to the -10th power. (More)

Question

Updated 2/7/2014 2:45:53 PM

1 Answer/Comment

12/5 divided by 7/2 is 24/35.

Added 2/7/2014 2:45:52 PM

This answer has been confirmed as correct and helpful.

simplify 3.5+8= **Weegy:** 3.5+8= 11.5 (More)

Question

Expert Answered

Updated 2/16/2014 8:35:05 AM

0 Answers/Comments

Evaluate this expression 1.7 - 2.3 + 9.3 = **Weegy:** 1.7 - 2.3 + 9.3 = 8.7 (More)

Question

Expert Answered

Updated 11/19/2014 10:32:32 AM

0 Answers/Comments

Simplify this 6t+2(1-5t)= **Weegy:** That would be 2-4t (More)

Question

Expert Answered

Updated 295 days ago|3/29/2021 2:54:02 PM

1 Answer/Comment

6t+2(1-5t)=

6t + 2 - 10t =

6t - 10t + 2 =

-4t +2.

6t + 2 - 10t =

6t - 10t + 2 =

-4t +2.

Added 295 days ago|3/29/2021 2:54:02 PM

This answer has been confirmed as correct and helpful.

Evaluate this y(x - 2) for x = 8 and y = 2 **Weegy:**
y(x - 2) for x = 8 and y = 2
2(8 - 2)
= 2(6)
= 12
(More)

Question

Expert Answered

Updated 6/18/2020 6:56:19 PM

0 Answers/Comments

35,130,708

questions answered

There are no comments.